1982
DOI: 10.1002/clc.4960051106
|View full text |Cite
|
Sign up to set email alerts
|

Acquired nonsurgical complete atrioventricular block in a child with endocardial cushion defect

Abstract: Summary: Acquired nonsurgical complete atrioventricular block is uncommon in children. We report an ll-year-old asymptomatic girl with endocardial cushion defect who gradually developed progressive conduction abnormality and complete atrioventricular block prior to open heart surgery. To our knowledge, a gradual progressive, nonsurgical, acquired atrioventricular block in endocardial cushion defect has not been described before. This report discusses the possible pathogenesis of acquired nonsurgical complete a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…We report on 2 cases -the first was a male child known to have had a proionged P-R interval ; the second was an I I year-old girl, who , 2 years before surgery, developed comp lete atrioventricular biock subsequen t Dr Received fo r pub lication: Jul y 7,1985 to first degree atrioventricular block . The clinical findings in the latter case have been reported previously (6).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…We report on 2 cases -the first was a male child known to have had a proionged P-R interval ; the second was an I I year-old girl, who , 2 years before surgery, developed comp lete atrioventricular biock subsequen t Dr Received fo r pub lication: Jul y 7,1985 to first degree atrioventricular block . The clinical findings in the latter case have been reported previously (6).…”
supporting
confidence: 62%
“…Furthermore, it has been reported that adults with atrioventricular sep tal defects can develop a progre ssive lengthening of the P-R inte rval which can lead to complete atrioventricular block (1 1, 13). Alth ough progre ssive heart block has been observed in adolescents with congenitally corre cted transposition (5 , 8) it is less well recognized in children with atrioventricular septal defect (6). Histological studi es on the cardiac conduction system of children with atriov entricular septal defect and atri oventricular conduction distu rbances recorded befo re submission to surgical repair are scarce.…”
mentioning
confidence: 99%
“…Both sinus node and AV nodal conduction abnormalities have been reported in patients with ASDs. Electrophysiologic markers of sinus node dysfunction have been described in many patients with ASDs (9,21). Clinical sinus node dysfunction has been reported both pre-and postprocedurally for ostium secundum ASDs and ostium primum ASDs (9).…”
Section: Conduction Disordersmentioning
confidence: 99%
“…Lesions particularly associated with inherent abnormalities of the conduction system include atrioventricular septal defects with common atrioventricular junction, visceral heterotaxy in the setting of isomeric atrial appendages, and lesions with discordant atrioventricular connections, as typically seen in congenitally corrected transposition. 1,2 Individuals with these lesions should be frequently evaluated for progression of disease afflicting the conduction system, even if they appear to have normal atrioventricular conduction at birth. The conduction system is thought to be vulnerable due to anatomic factors, such as the anterior and superior displacement of the atrioventricular node leading to a longer course of the bundle of His.…”
Section: Pacing For Bradycardiamentioning
confidence: 99%